Examining the Effects of Human Development, Unemployment, and Globalization on Obesity in the Community: Evidence from BRICS Countries. (13th March 2023) - Aydin, Mucahit; Aydin, Mehmet
Abstract : Obesity is a social problem that needs to be carefully considered regarding its causes and consequences. This study examines the impact of human development, unemployment, and globalization on obesity in BRICS (Brazil, Russia, India, China, and South Africa) countries from 1991 to 2016. For this aim, the study uses Fourier causality and cointegration tests, which consider smooth structural breaks. The cointegration test results show that obesity and explanatory variables do not move together in the long run for all countries. According to the causality result of this study, there is a unidirectional causal relationship from obesity to unemployment in China. On the other hand, there is unidirectional causality from obesity to human development and globalization in India. Overall, India can lessen the negative effects of obesity on its population and improve its standing in the global economy if it promotes healthy lifestyles and controls the food and beverage industry. On the other hand, obesity may cause people to become unemployed, so it is recommended that policymakers fight obesity to control unemployment in China.